1987
DOI: 10.1021/bi00398a006
|View full text |Cite
|
Sign up to set email alerts
|

Spin-label electron spin resonance study of bacteriophage M13 coat protein incorporation into mixed lipid bilayers

Abstract: The major coat protein of bacteriophage M13 was incorporated in mixed dimyristoylphosphatidylcholine/dimyristoylphosphatidylglycerol (80/20 w/w) vesicles probed with different spin-labeled phospholipids, labeled on the C-14 atom of the sn-2 chain. The specificity for a series of phospholipids was determined from a motionally restricted component seen in the electron spin resonance (ESR) spectra of vesicles with the coat protein incorporated. At 30 degrees C and pH 8, the fraction of motionally restricted phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
3

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
4
25
3
Order By: Relevance
“…In the absence of lipid the 50% saturation was achieved after 2.4 x 105 sec in the absence of lipids and after 8.7 x 104 in the presence of the lipid (Fig. 4 A and C) (15,41) or activation of lipases (36). One can speculate that class II MHC molecules may be found in different conformers within the cell, attaining an active binding state under the influence of component specific to subcellular microenvironments-e.g., in endosomes.…”
Section: Resultsmentioning
confidence: 91%
“…In the absence of lipid the 50% saturation was achieved after 2.4 x 105 sec in the absence of lipids and after 8.7 x 104 in the presence of the lipid (Fig. 4 A and C) (15,41) or activation of lipases (36). One can speculate that class II MHC molecules may be found in different conformers within the cell, attaining an active binding state under the influence of component specific to subcellular microenvironments-e.g., in endosomes.…”
Section: Resultsmentioning
confidence: 91%
“…A Digital Equipment Corp. LPS system and a dedicated PDP 11/10 computer with a VTll display were used to digitize the spectra. ESR spectrometer settings were those given in Datema et al (1987a).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have been able to incorporate M13 coat protein also in pure DMPC lipids so that now the lipid-protein interaction can be studied as a function of increasing content of negatively charged phospholipid. This is especially interesting, since in earlier experiments (Datema et al, 1987a) the protein was shown to have an increased specificity for negatively charged phospholipids.The present paper examines the effect of M 13 coat protein on mixed systems with variable amounts of DMPG and DMPC. The number of lipid association sites is determined in pure DMPC, as well as the relative association constants, for one representative spin-labeled phospholipid from each of the above three groups of phospholipids of different specificity.…”
mentioning
confidence: 87%
See 2 more Smart Citations